Perkhidmatan sokongan bagi keluarga yang mempunyai anak masalah pembelajaran di luar bandar - Aizan Sofia Amin,; Hasanatulakhma Mat Ayu,; Jamiah Manap, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aimed to explore the forms of support services received by families of children with learning disabilities. This study used a qualitative research approach of case study design, and it was conducted in a rural area of Kelantan. Five informants were interviewed in-depth, four of whom were mothers, and one was the father of children with learning disabilities. The data were transcribed verbatim and thematically analyzed. The results show that there are eight forms of support services received by families with children with learning disabilities. The support services are: 1) Community Rehabilitation Program, 2) Allowance or Financial Assistance, 3) Early Intervention, 4) Security (Conditional Infrastructure Provisioning), 5) Social Support, 6) Bus Services, 7) Counseling and Advisory Services and 8) Treatment and Medicine. Although most families received support services to support their children, there are still some limitations. The limitations were in terms of the provision of support services that may be due to the lack of proper cooperation from many parties whether involving government agencies, non-government and local communities. As a result, support services for families of children with learning disabilities need to be enhanced holistically and systematically.